2,6-Dichloro-4-nitroaniline –loaded Electrospun Cellulose Acetate Fiber Mats and Their Release Characteristics - Patcharaporn Thitiwongsawet; Paweena Ouykul; Akkarin Khaoroppan (Department of Chemical Engineering, Universitas Gadjah Mada, 2011)
Mats of cellulose acetate (CA) nanofibers containing 2,6-dichloro-4-nitroaniline (DCNA) were successfully fabricated by electrospinning from the neat CA solution (17% w/v in 2:1 acetone/dimethylacetamide) containing DCNA in various amounts (i.e. 5-15 wt. % based on the weight of CA). The morphological appearance of both the neat and the DCNA-loaded electrospun CA fibers were smooth and the incorporation of DCNA in the neat CA solution did not affect the morphology of the resulting fibers. The average diameters of the neat and the DCNA-loaded electrospun CA fibers ranged between 241-320 nm. The integrity of the as-loaded DCNA in the DCNA-loaded CA fiber mats was intact as verified by the 1H-nuclear magnetic resonance spectroscopic method. The amount of water retention, the amount of weight loss, and release characteristics of the DCNA-loaded CA fiber mats and the DCNA-loaded as-cast films in distilled water at 30Â°C were studied. The release characteristics were investigated by the total immersion method. The DCNA-loaded CA fiber mats exhibited greater amount of water retention, weight loss, and DCNA released than the DCNA-loaded as-cast films.